Evaluation of rice genotypes for acquired thermo-tolerance using Temperature Induction Response (TIR) technique - R, Beena; Vighneswaran, Veena; MC, Narayankutty (ORYZA-An International Journal of Rice, 2018)
Global climate change is leading to asymmetric atmospheric warming with reduced temperature differences between day and night. Increase in temperature alters broad range of physiological processes, such as growthand development, pollination and fertilization and ultimately affecting the yield. Hot summers in many agricultural regions can negatively affect the vegetative and reproductive growth phases of such crops and can result in up to 80% losses in rice yield. However, heat stress has numerous specific effects depending on the genotype. Physiological observations both under field and greenhouse conditions show a variable degree of tolerance between different genotypes. In this study, a screening protocol was developed based on the principle of "acquired tolerance" in which exposure of seedlings to a sub-lethal level of specific stress is used to induce tolerance to a subsequent lethal level of stress. Seedlings were subjected to a gradual temperature increase from38 to 48 °C for 3 h (induction treatment), immediately followed by challenging at 54°C for 3 h. Among the landraces, Njavara and Chenellu showed a mortality of 18 and 10% respectively, coupled with a less reduction in percent root and shoot growth when subjected to induction treatments. The physiological basis of thermotolerance in these lines was further confirmed, as these lines recorded a higher chlorophyll stability index and a strong antioxidant enzyme system with lesser lipid peroxidation in terms of malondialdehyde content values.